X-ray structure of the mature ectodomain of phogrin - Noguera, M.E. (2015)
Phogrin/IA-2β and ICA512/IA-2 are two paralogs receptor-type protein-tyrosine phosphatases (RPTP) that localize in secretory granules of various neuroendocrine cells. In pancreatic islet β-cells, they participate in the regulation of insulin secretion, ensuring proper granulogenesis, and β-cell proliferation. The role of their cytoplasmic tail has been partially unveiled, while that of their luminal region remains unclear. To advance the understanding of its structure-function relationship, the X-ray structure of the mature ectodomain of phogrin (ME phogrin) at pH 7.4 and 4.6 has been solved at 1.95- and 2.01-Å resolution, respectively. Similarly to the ME of ICA512, ME phogrin adopts a ferredoxin-like fold: a sheet of four antiparallel β-strands packed against two α-helices. Sequence conservation among vertebrates, plants and insects suggests that the structural similarity extends to all the receptor family. Crystallized ME phogrin is monomeric, in agreement with solution studies but in striking contrast with the behavior of homodimeric ME ICA512. The structural details that may cause the quaternary structure differences are analyzed. The results provide a basis for building models of the overall orientation and oligomerization state of the receptor in biological membranes.